Analisis Yuridis mengenai Prosedur dan Fungsi Hakim dalam Kasus Pidana Anak - Thoiman Nirwan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
Unlike adults, children are legal subjects in the criminal justice system and are entitled to specialtreatment. This complies with the principles of child protection contained in various internationalconventions, such as the UN Convention on the Rights of the Child, and domestic regulations, suchas Law Number 11 of 2012 on the Juvenile Justice System. The judge plays a very important role inhandling juvenile criminal cases in this situation. If a judge can provide balanced justice betweenthe interests of the child and society, it is important to thoroughly understand the procedures andfunctions of the judge in this case. This type of research is empirical legal research (sociological)that is descriptive in nature (describing) and does not aim to test hypotheses. This type of researchaligns with the objective of exploring legal principles, particularly those related to the duties andfunctions of judges in juvenile criminal trials and the rights of children in juvenile criminal cases.